Gas chromatography-mass spectrometry in the taxonomy of Miscanthus - N. M. Slynko; N. V. Burmakina; O. M. Potseluyev; S. Yu. Kapustyanchik; G. Yu. Galitsin; T. N. Goryachkovskaya; L. V. Kuybida; S. V. Shekhovtsov; S. E. Peltek; V. K. Shumny (Вавиловский журнал генетики и селекции)
Chemotaxonomy as a system approach deals with intra- and interspecific polymorphism of a group of taxa in order to clarify their taxonomic positions or to select material for selection or introduction. In this study we performed chemotaxonomic analysis of specimens of Miscanthus sinensis and M. sacchariflorus collected in the Russian Far East and of hybrid plants of both natural and artificial origin. We found 153 substances and identified 143 of them in extracts of eleven Miscanthus plants by gas chromatography-mass spectrometry (GC-MS). These substances can be grouped into alkanes (20 compounds), fatty acids (34), phenols (13), sterols (18) toсopherols (8), norterpenoids (12), and phytols (13), as well as their derivatives. The main components of the extracts of miscanthus samples are fatty acids and their derivatives (total content 19.94–41.02 %), dominated by palmitic and linolenic acids, and sterols (mainly β-sitosterol, stigmasterol, and α-amyrin), which constitute 17.15–31.73 %. The values of the CPI “oddness index” for the alkane components of the extracts were within 1.55–7.18, with extracts from leaves of the Far Eastern samples characterized by the lower half of this range (1.55–2.74), while extracts from leaves of hybrids fell to the upper half (5.78–7.18). Principal component analysis of extraction profiles allowed us to separate three distinct clusters: M. sinensis, M. sachariflorus, and their hybrids, as well as to verify the origin of one of the natural hybrids. The results of chemotaxonomic analysis mostly matched those of DNA sequencing of a fragment of the plastid genome, which, moreover, allowed us to identify the species nature of the maternal plants used to obtain these hybrids. Chemotaxonomic analysis using GC-MS was found to be an efficient additional technique to delimit various morphological forms of M. sinensis, M. sachariflorus, and their hybrids.